Enabling of Component Identification by High Speed Measuring of Grinding Wheel Topography. (2016) - Breidenstein, B.; Denkena, B.; Grove, T.; Hockauf, R.
Abstract: The machining process affects quality and function of components. For this reason, it is an important key competence of the manufacturer. Over the past years, counterfeit products have been threatening the user and damaged the reputation of the original manufacturer. On this account, a method of fingerprinting of ground surfaces was developed in the Collaborative Research Center 653 to protect components against plagiarism. However, this method needs the measuring of every single ground surface, which means a huge expenditure of time in the production chain. If it were possible to predict the grinding surface of the grinding tool precisely, occasional measurements of the grinding tool during the setup time would be sufficient to assign the right tool to the component's surface and the manufacturer behind it. The presented paper is focusing on methods for the determination of the topography of grinding tools. These topographies enable the manufacturer to predict and thus identify the surface of components.